2018
DOI: 10.21037/jtd.2018.05.119
|View full text |Cite
|
Sign up to set email alerts
|

Tubeless single-port thoracoscopic sublobar resection: indication and safety

Abstract: Our tubeless protocol utilizes DDS to select patients who can have intercostal drainage omitted after non-intubated single-port VATS for pulmonary resection. Using objective DDS parameters, we believe that this is an effective way to reduce the rate of pneumothorax after tubeless single-port VATS in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…All the results showed that patients operated upon under spontaneous ventilation had a shorter postoperative recovery time when compared with the conventional VATS approach. The other two clinical trials also observed a more encouraging response in patients after using this method . In patients where muscle relaxants were not used during surgery, the most obvious advantage of nonintubated anesthesia was that it could reduce postoperative respiratory complications, promote early postoperative activities and earlier oral feeding.…”
Section: Nonintubated Anesthesiamentioning
confidence: 99%
See 1 more Smart Citation
“…All the results showed that patients operated upon under spontaneous ventilation had a shorter postoperative recovery time when compared with the conventional VATS approach. The other two clinical trials also observed a more encouraging response in patients after using this method . In patients where muscle relaxants were not used during surgery, the most obvious advantage of nonintubated anesthesia was that it could reduce postoperative respiratory complications, promote early postoperative activities and earlier oral feeding.…”
Section: Nonintubated Anesthesiamentioning
confidence: 99%
“…In a single center study reported by Lai et al ., they used a Foley catheter ( n = 441 patients) instead of a 28‐F chest tube ( n = 223 patients) after VATS lobectomy resulting in a statistically significant reduction in pain, shortened mean days until chest tube removal after lobectomy and a smaller proportion of disordered wound healing at the drainage site. The potential benefits of avoiding chest drains are reduced pain, discomfort, and incidence of respiratory complications (Table ).…”
Section: Nonchest Tube Drainagementioning
confidence: 99%
“…However, the main pitfall of omitting chest tube placement was residual pneumothorax. [7][8][9] Although the incidence of postoperative pneumothorax has been reported to range from 7.6 to $20% in the literature, a relatively higher percentage of postoperative pneumothorax (40%) has been observed in previous studies. 9,10 In thymectomy, the pulmonary is intact in most cases, and the incidence of pneumothorax is rare.…”
Section: Discussionmentioning
confidence: 93%
“…Non-intubated anaesthesia might prevent the adverse events caused by intubation, ventilation and extubation procedure [ 1 ]. Tubeless approach could further relieve wound pain associated with chest tube placement [ 2 ]. However, full expansion of lung sometimes could not be achieved after operation and presented as pneumothorax [ 3 ].…”
Section: Introductionmentioning
confidence: 99%